(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
The author deals with the problem of criminal measures and sanctions in the legislation of the Republic of Serbia during the Covid-19 pandemic. The executive branch of the government declared a state of emergency in the Republic of Serbia in March 2020. At the same time the so-called Crisis Headquarter was established with the authority to impose measures of criminal-legal nature. During the two-month state of emergency, through the Crisis Headquarter, the executive branch of the government was changing criminal laws and sanctions at an almost daily basis. It is debatable whether such laws meet the rule of law and the European Court of Human Rights standards. Many citizens failed to adapt their behavior to the imposed measures. On the one hand, the courts have fallen into the trap of double punishment, both for a crime and for a misdemeanor. On the other hand, justifications of the courts’ decisions are also questionable, especially those containing references to statements made by members of the crisis team through the media. Furthermore, the Constitutional Court didn’t rule on any of the numerous requests for constitutional review, but in September it came out with the view that since the state of emergency was over, its decision was unnecessary. The paper is comprised of several units. In the first place, the author explains the process of legal changes by analyzing all the laws and rules that were passed by the end of 2020, as well as data related to the punishment of residents whose behavior was not in accordance with existing legal solutions. Bearing in mind the standards of the rule of law and the European Court of Human Rights, the author then explains that the measures implemented by the Serbian authorities do not meet the basic required criteria, primarily the foreseeability of the law, as well as that the laws were abused for the purpose of the election campaign. The special attention is paid to curfews and the complete ban on leaving homes for senior citizens well as ban of contacting with the family members, and then the lockdown of the rest of the population. The actions taken by the authorities during the epidemic resulted in violation of human rights of their citizens, and experience shows that the only court that citizens will be able to turn to will be the European Court of Human Rights. The author believes that with this understanding of the law and respect for its own citizens, the European Union can only be a distant idea.